Dualismos e dualidades nas experiências umbandistas em um terreiro no Rio Grande do Sul - Pires, Helaysa Kurtz Gressler (2015)
This work presents the results in progress of an ethnography realizedin 2012-2015 in a temple [terreiro] of ”esoteric” umbanda [umbanda esotérica] in the inlands of Rio Grande do Sul, South of Brazil, and aims to reflect on its manifest contradictions around systematizing and practising mediumship. Understood as a relation between material/body and spirit, we‟ve been confronted to a variety of dualisms - that disjoin them -, and dualities, that articulate them in a tension. The fieldwork display a dualistic discourse that establishes a hierarchy, in which the spiritual is clearly privileged on the material, although the practices – incorporation experiences – lead us to question and rethink this hierarchy, in re-considering them as dualities. In these conditions, the interpretation of this religious system as a “therapeutic pattern”seems pertinent, since practices can result in healing, or produce transformation and “metamorphosis”. This interpretation leads to the secular distinction between science and religion. These questions also appear in the ethnographical encounter of the researcher/practicing umbandista, in between its research‟s experiences and its religious‟ ones. As a result, our hypothesis is that these metamorphoses are unrolled via a process given by “a spiritualization of the material” and a “materialization of the spiritual” that release a set of strangeness states inherent to the liminalities existing in the mediums‟ status changes. These changesmake them face themselves with their own limits. These status changes, beyond the transformations of the medium they provoke, also launch changes in the terreiro‟s community, inviting us to reflect about the concept of communitas. This process is described in the first part, when we expose the context in which the terreiro was created, its foundation by a medium become a cacique-chief [cacique-chefe] and the construction of its physical space by the members of the group. This religious leader‟sideological orientations, and consequently, the community‟s ones, are described in their context in the second part, when we trace the terreiro‟s genealogy. The several umbandasthat compose its origins denote an ideological quarrel for its legitimacy through cosmologies affiliated either to kardecist discourses, either to afro-braziliantraditions. In the light of this, the group created this image of “umbanda of knowledge” [umbanda do conhecimento], promoting studies that, in tension with practice, defy them for an articulation of the “doctrines” [doutrinas] and “having one's feet firmly on the ground » [pé no chão do terreiro]. This challenge is quite similar to the “magic of the anthropologist” as elaborated by VagnerGonçalves, a theoretical explanation of what the former are learning observing terreiros.Learning, studying, experiencing are summed in the fourth part, leading us to the interpretation of the given experiences through mediumshipas “pattern of healing”, through which the medium turn himself into its agent. From this, we elaborated the idea of “estar no corpo” as a process of metamorphosis in which materiality and spirituality seem to transform the sufferingin something making the medium prosper. We conclude opening our interpretations to the technical aspect of the experiences, as “estar no corpo” [being in the body] include as much singular responses to “ser o corpo” [being the body], as it makes of the body a handling object - “ter um corpo” [having a body] -by a “bodily technic”.